Ingeniería didáctica y su influencia en el aprendizaje de funciones en los estudiantes de la Universidad Nacional Micaela Bastidas de Apurímac - Ecos Espino, Alejandro Manuel (2018)
This research presents the results of the application of a didactic engineering, designed with the aim of improving learning the concept of function in students of the National University of Apurimac Micaela Bastidas. For engineering design took as reference the Theory of Didactic Situations proposed by G. Brosseau and the Theory of Semiotics Representation Records posed by R. Duval. They conducted a cognitive analysis of the conceptions of students regarding the concept of function, a training analysis on how this concept was in the curricula and textbooks, and an epistemological analysis to identify how the concept was to evolve into a more elaborate definition. The above analysis allowed the identification of significant variables and evaluate the design of six teaching situations were worked with students. The experimental process was carried out with the participation of students of lower academic studies at the School of Engineering Professional Agroindustrial, to which they are initially applied a pre-test, and post test after experimentation. The results obtained show that the application of didactic engineering allowed significantly improve student learning about the concept of function in relation to the management of records of verbal representation, tabular, graphical and algebraic, with 95 % confidence, validated through the test statistic T Students. Furthermore, it was verified that the application of didactic engineering allowed the 91 % of students regularly exceed the level of learning and improve the various skills that will enable conversion between different registers of representation of the concept of function, such as interpretation graphs, interpreting formulas, numerical adjustments, calculate values ​​, among others.